Analisis Faktor-Faktor yang Mempengaruhi Kepuasan dan Motivasi Kerja Karyawan pada Perusahaan Ritel - Rifqy Hafizh Priandy; Anisa Nur Azizah; Putri Rahayu; Wahidin; Dwi Andryansyah; Muhamad Kosim (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to identify and analyze the factors influencing employee job satisfaction in retail companies. A qualitative descriptive approach was employed, with data collected through in-depth interviews with employees from various departments within a retail company. The findings reveal several key factors affecting job satisfaction, including a conducive work environment, harmonious relationships between colleagues and supervisors, recognition and appreciation for performance, and a healthy work-life balance. These findings indicate that retail companies need to pay attention to non-financial aspects that directly impact employee motivation and comfort. By understanding these factors, companies can enhance employee performance and reduce turnover rates. This study is expected to serve as a reference for retail management in formulating policies that support employee well-being and productivity.